Confidence in the police by race: taking stock and charting new directions. (2nd January 2019) - Cao, Liqun; Wu, Yuning
Abstract: The current study reflects a narrative mega-review of confidence in the police by race. This review has led to two conclusions. First, blacks and whites have different levels of confidence in the police, but the difference between races is a matter of degrees. Second, race is not the strongest predictor of confidence in the police in most multivariate analyses. When variables, such as police contacts and concentrated disadvantage, are controlled for, the effect of race tends to be attenuated and/or sometimes disappear. These results prompt us to urge scholars to chart new directions for future research: fairness and its flip side – injustice – rather than race should be the focus of empirical and analytical gaze. The practical implications derived from this review are twofold. First, central to improving minority confidence in the police is to treat people of all racial groups fairly and equitably. Second, the police and the policed must come to terms and have faith in our democratic system and reform. This review is the first of its kind. We conclude by proposing a template of explaining confidence in the police by race with fairness as the tying knot.